Community of practice: shared purpose, shared knowledge. (2nd August 2019) - Henry, Claire; Cooper, Marie; Hayes, Anita
Abstract : Working and learning together is the best way forward for professional development and to address industry-specific issues. Claire Henry, Marie Cooper and Anita Hayes describe their work in setting up community of practice networks and discuss three examples.